Análise dos parâmetros de harmonia facial e dentária em jovens mulheres brasileiras - Saab, Rafaella Caramori (2019)
The objectives of this thesis, presented in manuscript format, were: 1. To identify aesthetic parameters of facial and dental harmony (facial, smile-face, smile and dental proportions) and to identify the association of these proportions with the different types of face in a population of young women (Manuscript 1); 2. To evaluate the perception of facial aesthetics and smile of young women by lay people and specialists in different areas of dentistry (Manuscript 2). For this thesis, a convenience sample of 103 young Brazilian women (from the southern region of Brazil), dental students, aged 18 to 31 years was selected. For the analysis of the aesthetic parameters (aesthetic proportions), three standardized photographs were taken: frontal of the face without smiling, frontal of the smiling face and an approximate photo of the smile. The images were analyzed using Adobe PhotoShop CS4 software and the measurements were obtained by means of anatomical points and linear tracings, and expressed as proportions (facial, smile-face, smile and dental proportions). For manuscript 1, according to the height/width ratio found, the individuals were categorized as medium, long or short faces. Then, associations between the proportions evaluated for the different face types were established by multivariate linear regression (α=0,05). Most of the sample was classified as medium face, and presented normality in the evaluated proportions. It can be observed that there was a significant association between facial and dental proportions and different types of face (p <0.05). The individuals with short faces presented reduction of the middle third of the face, decrease of the space between the lips in the smile and decrease of the external height of the lips in the smile, compared to the individuals of the middle face. In long-faced individuals there was a decrease in upper lip length or an increase in lower lip length compared to middle-face individuals. Regarding dental proportions, long-faced individuals had significantly higher central incisor height than middle-faced individuals. For manuscript 2, from the photographs of the 103 young women, two facial proportions were obtained: height/width of the face and proportion of the thirds of the face (upper third + middle third/lower third). Afterwards, 30 images (10 photographs face without smile, 10 smiling face and 10 of smile) were selected from 5 volunteers considered harmonic (measures of proportions closer to the golden ratio 1.618) and 5 volunteers considered non-harmonic (proportions evaluated discrepant in relation to the proportion golden). The images were randomly arranged (harmonic or non-harmonic) in a Google platform form for further evaluation of the attractiveness of lay people and experts in different areas of dentistry. Individually, the images were evaluated by assigning concepts from 0 not pleasant to 10 very pleasant. Next, the evaluators selected two images, one considered most attractive and one less attractive. Data were subjected to statistical analysis (Mann-Whitney, Kruskall Wallis and Chi-square tests, with a significance level of 5%. A total of 144 people performed the evaluation of the photographs, of which 97 (60.6%) were female and 47 (29.4%) were male. The age of respondents ranged from 21 to 62 years (mean age 35.22 ± 9.04 years). Thirty-two (20%) individuals were lay people (not trained in dentistry) and 112 (70%) graduated in dentistry, of which 21 (13.1%) had a specialty in Restorative Dentistry, 25 (15.6%) in Surgery, 35 (21.9%) in Orthodontics and 31 (19.4%) in Prosthesis. Significant difference could be observed between the medians of the images considered harmonic and non-harmonic in the pictures without smiling, smiling and of smile, regardless of gender, age and background. Higher values were observed for the harmonic images compared to the non-harmonic ones. There was no difference in aesthetic perception among lay people and dentists for harmonic and non-harmonic images in photos without smiling, smiling or of smile. Regarding the different specialties evaluated, there was significant difference only in the non-harmonic images of the smiling photos, where higher values were attributed by the Prosthesis specialists, differing from the specialties of Buccomaxillofacial Surgery and Orthodontics. It could be observed that for all photos the most voted images as attractive were those considered harmonic. And the most voted images as least attractive were those considered non-harmonic. Based on the results obtained from this thesis, it can be concluded that the population evaluated was mostly within the parameters considered harmonic for facial, smile-face, smile and dental proportions, and that there was a significant association of facial and dental proportions for the different types of face. In evaluating the aesthetic perception of the parameters of the population evaluated, in general there was no significant difference between the evaluators, regardless of gender, age, education in dentistry and specialty. Most evaluators selected harmonic images as more attractive compared to nonharmonic ones.